METODE ADI (ALTERNATING DIRECT IMPLICIT) PADA PENYELESAIAN MODEL ALIRAN AIR TANAH - Mohammad Syaiful Pradana; Lutvia Muniroh (Unisda Journal of Mathematics and Computer Science (UJMC), 2016)
The flow of water beneath the earth's surface flows through the pores like rocks and other porous media that can be flooded by water. In the soil, water flows due to the difference in hydraulic height that is the difference from ground water level. Groundwater movement, generally moving water with relatively slow flow can be modeled using Darcy law and mass conservation laws. The model is approximated numerically using the Finite Difference Method with the ADI (Alternating Direct Implicit) scheme. The ADI method has an advantage in the accuracy or accuracy of the results and the speed of completion. The ADI method can be applied to two or three dimensional systems to obtain the tridiagonal coefficient matrix.